Financial Inclusion in Sub-Saharan Africa: Recent Trends and Determinants. Issue 1 (2nd January 2019) - Asuming, Patrick Opoku; Osei-Agyei, Lotus Gyamfuah; Mohammed, Jabir Ibrahim
ABSTRACT: This paper conducts a comparative analysis of financial inclusion in 31 Sub-Saharan African countries using data from the global Findex database. We find that while the aggregate level of financial inclusion has increased significantly between 2011 and 2014, there are variations in both the level and rates of improvement among the countries. We also find that individual-level covariates (age, education, gender and wealth), macroeconomic variables (growth rate of GDP and presence of financial institutions) and Business Freedom are significant predictors of financial inclusion. Our findings suggest that financial inclusion policies should target key populations like women and young people.